Monsoon Agriculture - Suggestieve Methods Using Dependable Inflow & Rainfall for a Command Area - Surianarayanan, S; Jaya kumar, S; Jeyaprakash, S (International Journal of Engineering and Technology, 2018)
In the recent trend of changing environment, the rainfall and the inflow to the reservoir are getting reduced year by year respectively in agricultural field and in river basins. In this paper the dependable inflow into the reservoir and the rainfall in the command area is estimated with the past 30 years data. The statistical methods and formulae (Variance, Mann- Kendall method) are used to determine the dependable inflow and rainfall for both the monsoons. It is found that the inflow is not dependable for South â€“West monsoon, to do the agriculture, for a normal crop, with medium water requirement.. For the North - East monsoon both the inflow and rainfall are dependable hence the agriculture can be carried out with a single crop (paddy) having more water requirement (or) possible multi-crops, according to the storage in the reservoir and prediction of rainfall in that season. The deductions for other requirements of the dam, losses for evaporation, conveyance etc has been taken into account. The case study is done with the data for 30 years (1982-2012)for a dam in Tamil Nadu, India.Â